Identification and Expression Analysis of the Alfin-like Gene Family in Tomato and the Role of SlAL3 in Salt and Drought Stresses - Ruixin Jin; Juan Wang; Bin Guo; Tao Yang; Jiahui Hu; Baike Wang; Qinghui Yu (Plants, 2023)
Alfin-like (AL) transcription factors are a family of plant-specific genes with a PHD-finger-like structural domain at the C-terminus and a DUF3594 structural domain at the N-terminus that play important roles in plant development and stress response. In the present study, genome-wide identification and analysis were performed of the AL protein family in cultivated tomato (Solanum lycopersicum) and three wild relatives (S. pennellii, S. pimpinellifolium, and S. lycopersicoides) to evaluate their response to different abiotic stresses. A total of 39 ALs were identified and classified into four groups and based on phylogenetic tree and evolutionary analysis were shown to have formed prior to the differentiation of monocotyledons and dicots. Moreover, cis-acting element analysis revealed that various phytohormone response and abiotic stress response elements were highly existed in tomato. In addition, further analysis of the SlAL3 gene revealed that its expression was induced by drought and salt stresses and localized to the nucleus. In conclusion, our findings concerning AL genes provide useful information for further studies on their functions and regulatory mechanisms and provide theoretical references for studying AL gene response to abiotic stresses in plants.